2023
DOI: 10.3390/antiox12081494
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Four Functional Feed Additives on Growth, Serum Biochemistry, Antioxidant Capacity, Gene Expressions, Histomorphology, Digestive Enzyme Activities and Disease Resistance in Juvenile Olive Flounder, Paralichthys olivaceus

Abstract: An 8-week feeding trial was executed to evaluate the efficacy of four functional feed additives in replacing antibiotics in juvenile olive flounder, Paralichthys olivaceus, fed with a low-fish-meal diet. A basal diet without feed additives was used as a control (CON); other diets were formulated by supplementing 0.50% taurine (TW), 0.30% peptide (PT), 0.23% mineral water (MW), 0.35% yeast-extracted nucleotides (GRO), 0.35% GRO + 0.50% taurine (GROTW), 0.35% GRO + 0.30% peptide (GROPT) and 0.35% GRO + 0.23% min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Similarly, Ullah et al 26 reported that the chemical compositions of the dorsal muscles and the entire body did not differ significantly across the groups fed a diet supplemented with lauric acid. Choi et al 27 reported that there is no effect of four functional feed additives on body composition in juvenile olive Flounder.‏ However, these results are incompatible with those of Attalla et al 28 , who reported that the body composition of Nile tilapia fish fed feed additives showed a drop in fat percentage and an increase in protein content. Moreover, in contrast to Eissa et al 24 , the body composition study showed no alterations in lipid contents with probiotic treatment.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Similarly, Ullah et al 26 reported that the chemical compositions of the dorsal muscles and the entire body did not differ significantly across the groups fed a diet supplemented with lauric acid. Choi et al 27 reported that there is no effect of four functional feed additives on body composition in juvenile olive Flounder.‏ However, these results are incompatible with those of Attalla et al 28 , who reported that the body composition of Nile tilapia fish fed feed additives showed a drop in fat percentage and an increase in protein content. Moreover, in contrast to Eissa et al 24 , the body composition study showed no alterations in lipid contents with probiotic treatment.…”
Section: Discussionmentioning
confidence: 91%
“…The levels of blood proteins and albumin in Nile tilapia improved with the supplementation of some safe feed additives 48 . To the contrary, Choi et al 27 reported that combinations of four feed additives did not affect serum proteins. Regarding results of kidney function, serum creatinine and urea decreased when feed additives were used alone, as recorded by Youssef et al 49 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation